Optimizing Differentiated Learning in Physical Education Subjects: Utilization of Information and Communication Technology (ICT) - Lucius, Rino Lusiyono; Daryanto, Zusyah Porja (Indonesian Journal of Physical Education and Sport Science, 2024)
Study Purpose. The research explores the effectiveness of differentiated learning strategies in addressing obstacles encountered by students in physical education. It focuses on tailoring teaching methods to accommodate individual differences in readiness, learning profiles, and interests, aiming to enhance engagement and learning outcomes.Materials and methods. Using qualitative methods, including interviews and observational analysis, the study investigates the impact of differentiated learning, particularly through the use of Information and Communication Technology (ICT) in rhythmic gymnastics instruction. Observations suggest that video-assisted instruction increases student interest and engagement, facilitates self-reflection and promotes autonomy.Results. The findings highlight the positive influence of differentiated learning on engagement and learning outcomes, promoting equity and inclusion in the classroom.Conclutions. The study underscores the importance of adapting teaching methods to meet students' diverse needs, ultimately contributing to their overall well-being in physical education and beyond.